2005
DOI: 10.2320/matertrans.46.1839
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Retained Austenite on Tensile Properties of Steels with Bainitic Microstructures

Abstract: In high-carbon, silicon-rich steels it is possible to obtain a very fine bainitic microstructure by transformation at low temperatures (200-300 C). This microstructure consists of slender ferrite plates, with thicknesses of several tens of nm, in a matrix of retained austenite. Whereas strength is mainly provided by to the fine scale of the ferrite plates (stronger phase), ductility is mostly controlled by the retained austenite (softer phase). Further improvement in ductility is achieved by strain induced tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(121 citation statements)
references
References 23 publications
7
112
0
2
Order By: Relevance
“…These findings explain the observed low ductility in steel 1 and support the earlier suggestion on the strong effect of chemical composition of the RA in nanostructured bainitic steels on their ductility. [58] B. TRIP Steel 3…”
Section: Comparison Of the Mechanical Behavior Of Nanobainitic Steelsmentioning
confidence: 99%
“…These findings explain the observed low ductility in steel 1 and support the earlier suggestion on the strong effect of chemical composition of the RA in nanostructured bainitic steels on their ductility. [58] B. TRIP Steel 3…”
Section: Comparison Of the Mechanical Behavior Of Nanobainitic Steelsmentioning
confidence: 99%
“…A prominent feature is that they all fail when the retained austenite content is reduced to about 10%. An Table 1 T I , V γ , σ Y and σ U T S stand for isothermal transformation temperature, the volume fraction of retained austenite, the 0.2% proof and ultimate tensile strengths respectively [24].…”
Section: Nanostructured Bainitementioning
confidence: 99%
“…More recent work, based on measurements of retained austenite content before tensile tests and calculated evolutions, proposed that the stability of retained austenite would influence the material ductility, and indicated that there could be an optimum stability [20]. Data from this same publication were later re-interpreted to propose the existence of a percolation mechanism, whereby ductility was imparted by a percolating network of retained austenite in the matrix of bainitic ferrite, and fracture occurred at an approximately constant volume fraction of 10% retained austenite [17].…”
Section: Introductionmentioning
confidence: 99%